# Factorize the algebraic expression $9a^2-24ab+16b^2$.

Given:

The given algebraic expression is $9a^2-24ab+16b^2$.

To do:

We have to factorize the expression $9a^2-24ab+16b^2$.

Solution:

Factorizing algebraic expressions:

Factorizing an algebraic expression means writing the expression as a product of two or more factors. Factorization is the reverse of distribution.

An algebraic expression is factored completely when it is written as a product of prime factors.

$9a^2-24ab+16b^2$ can be written as,

$9a^2-24ab+16b^2=(3a)^2-2(3a)(4b)+(4b)^2$             [Since $9a^2=(3a)^2, 16b^2=(4b)^2$ and $24ab=2(3a)(4b)$]

Here, we can observe that the given expression is of the form $m^2-2mn+n^2$. So, by using the formula $(m-n)^2=m^2-2mn+n^2$, we can factorize the given expression.

Here,

$m=3a$ and $n=4b$

Therefore,

$9a^2-24ab+16b^2=(3a)^2-2(3a)(4b)+(4b)^2$

$9a^2-24ab+16b^2=(3a-4b)^2$

$9a^2-24ab+16b^2=(3a-4b)(3a-4b)$

Hence, the given expression can be factorized as $(3a-4b)(3a-4b)$.

Updated on: 09-Apr-2023

57 Views